Efficacy of NETDC (New England Trophoblastic Disease Center) prognostic index score to predict gestational trophoblastic tumor from hydatidiform mole (Faculty of Medicine Universitas Indonesia, 2004)
A prospective longitudinal analytic study assessing the efficacy of NETDC (New England Trophoblastic Disease Center) prognostic index score in predicting malignancy after hydatidiform mole had been performed. Of the parameter evaluated; age of patients, type of hydatidiform mole, uterine enlargement, serum hCG level, lutein cyst, and presence of complicating factors were significant risk factors for malignancy after hydatidiform mole were evacuated (p<0.032). The study were done on 50 women diagnosed with hydatidiform mole with 1 year observation (January 2001-December 2002) at the Department of Obstetrics and Gynecology, Mohammad Hoesin Hospital, Palembang. The results showed that the NETDC prognostic index score predicted malignancy in 50% of high risk group and 10% in low risk group (p<0.05). This showed a higher number than that found by the WHO (19%-30%). The risk for incidence of malignancy after hydatidiform mole in the high risk group is 9.0 times higher compared to that of the low risk group (CI: 1.769-45.786). (Med J Indones 2004; 13: 40-6) Keywords: New England Trophoblastic Disease Center (NETDC), gestational trophoblastic tumor, hydatidiform mole, high and low risk